Understanding of Colistin Usage in Food Animals and Available Detection Techniques: A Review - Kumar, Harsh; Chen, Bing-Huei; Kuca, Kamil; Nepovimova, Eugenie; Kaushal, Ankur; Nagraik, Rupak; Bhatia, Shashi Kant; Dhanjal, Daljeet Singh; Kumar, Vinod; Kumar, Anil; Upadhyay, Navneet Kumar; Verma, Rachna; et al. (Animals, 2020)
Progress in the medical profession is determined by the achievements and effectiveness of new antibiotics in the treatment of microbial infections. However, the development of multiple-drug resistance in numerous bacteria, especially Gram-negative bacteria, has limited the treatment options. Due to this resistance, the resurgence of cyclic polypeptide drugs like colistin remains the only option. The drug, colistin, is a well-known growth inhibitor of Gram-negative bacteria like Acinetobacter baumanni, Enterobacter cloacae, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Technological advancements have uncovered the role of the mcr-1(mobilized colistin resistance) gene, which is responsible for the development of resistance in Gram-negative bacteria, which make them distinct from other bacteria without this gene. Additionally, food animals have been determined to be the reservoir for colistin resistance microbes, from which they spread to other hosts. Due to the adverse effects of colistin, many developed countries have prohibited its usage in animal foods, but developing countries are still using colistin in animal food production, thereby imposing a major risk to the public health. Therefore, there is a need for implementation of sustainable measures in livestock farms to prevent microbial infection. This review highlights the negative effects (increased resistance) of colistin consumption and emphasizes the different approaches used for detecting colistin in animal-based foods as well as the challenges associated with its detection.
Keywords: detection methods; antibiotics; food animals; colistin; multi-drug resistance